Hands-On Contextual Learning Experimentation on Psychomotor Abilities - Billyardi Ramdhan (Jurnal Report of Biological Education, 2020)
The purpose of this study was to determine the effect of contextual learning models based on hands-on activities on students' psychomotor abilities. This type of research is a quasi-experimental using pretest posttest control group design. The results showed the psychomotor ability of students in the experimental class averaged 79.63 which was categorized as "good" while the control class obtained an average of 68.93 which was also categorized as "good". Hypothesis testing using t test shows the results of tcount = 4.73 while the t table = 2.002 so that H0 is rejected and Ha is accepted. This means that there is a significant difference between learning using hands-on contextual learning models compared to contextual learning models based on conventional practicum student psychomotor abilities. The results of the correlation coefficient test, the experimental class got the value of rxy = 0.9965 and the contribution was 99.30% while the control class was rxy = 0.987 and the contribution was 97.42% with the value of r (0.05) (30) = 0.361. Thus rcount> rtable which means that there is a very strong relationship between psychomotor abilities and cognitive knowledge on water pollution material based on the interpretation coefficient interpretation table in the two classes.